Cubosomes as Carriers for MRI Contrast Agents - Alcaraz, Nicolas; J. Boyd, Ben (Current Medicinal Chemistry, 2017)
Cubosomes are self-assembled nanostructures that often form on dispersion of polar lipids in aqueous environments. The nanoparticles are analogous to liposomes but contain a complex internal self-assembled structure providing a point of difference to relatively simple liposomes. They exhibit a range of attractive properties such as having a high surface area, being able to incorporate both hydrophobic and hydrophilic molecules and controlled release. Consequently cubosomes are of increasing interest in fields such as drug delivery, and diagnostic imaging, in particular as a carrier for magnetic resonance imaging contrast agents. Over the last decade the incorporation of various contrast agents into the cubic mesophases has demonstrated improved relaxivity and resolution, as well as addressing other limitations of commercially available agents by increasing circulation time, stability and targeting. This minireview provides a brief overview of what cubosomes are, how they can be made, how they are characterised and also summarise the findings from the studies that have used cubosomes to develop better contrast agents for MRI, as well as highlight some potential for future developments.
Keywords: lipid